Análisis sobre el uso de los dispositivos móviles en la comunicación familiar en la comunidad del Sector San Andrés Dos, Parroquia Siete de Octubre del cantón Quevedo, año 2021 - Mayia Cagua, Milena Michell (2021)
The use of mobile devices and their technological advances have brought many benefits to the human being, but also through this it has generated a great distance in family communication, especially the behavior of parents and adolescents. The current problem in the family members, specifically in the San Andrés Dos of the Quevedo Canton, affects the lack of communication and sharing family anion. The methodology that was applied in the research was though the quantitative method that was given though an Online survey conducted to parents and adolescents in the San Andrés Dos sector, giving the result of a negative objection regarding parents and adolescents who do not care about the correct use of mobile devices and that there is distancing in family communication.